Devotion and Defiance : My Journey in Love, Faith and Politics - Shahid, Humaira Awais (New York W. W. NORTON & COMPANY, 2014)
In this warm and intimate memoir, Humaira Awais Shahid tells her inspiring story. A bookish young woman who identified with the independent-minded heroines of Jane Austen and Virginia Woolf, she never dreamed that love would lead her to become the most prominent Muslim woman activist and legislator for women's rights in Pakistan. After falling for the son of a prominent newspaper family, Shahid joined the family business. She soon revamped the insipid "women's pages" of one of Pakistan's leading newspapers into a crusading force for exposing the abuses suffered by Pakistani women and girls. Determined to bring meaningful change to the lives of Pakistan's most disenfranchised, she sought and won a seat on the Punjab Provincial Assembly. There, she rose above collective apathy and targeted intimidation to battle corruption, champion bold legislation, change minds and claim breathtaking victories. In the end, faith and family would sustain her conviction that it takes just one person to better the lives of many.
Include Index
Keywords: Women--Social conditions -- Pakistan -- Women and religion